DESIGN OF A COOLING SYSTEM FROM UNDERGROUND THERMAL ENERGY STORAGE (UTES, UNDERGROUND) THERMAL ENERGY STORAGE) BASED ON EXPERIMENTAL RESULTS - Barros Enriquez, José David; Villafuerte Lopez, Milton Ivan; Punina Guerrero , Diego Javier; Garcia Saquicela , Marcelo Rodrigo (Journal of Applied Engineering Science, 2024)
Geothermal energy is a renewable and clean source that has been used for electricity generation in some countries since the 50s, the main characteristic to be used in this application is that the subsoil must have a high temperature geothermal resource (+150 °C). However, it can also be used in applications such as air conditioning in places where the temperature is around 30°C; In Europe alone, there are more than one million thermal installations operating by harnessing geothermal energy. The objective of the work was to design a cooling system from the storage of underground energy, for that, it is essential to know the variation of subsoil temperatures during a certain period of time. For this purpose, sensors were used that were installed at different depths and by means of an Arduino, information of a whole year was stored; so that these data are as representative as possible of the energy storage conditions and the changes depending on the seasons that pass. Additionally, the characteristics of the soil (conductivity, humidity and composition) were taken into account, where the equipment is intended to be installed in subsequent works. For the determination of the necessary cooling load, the design requirements of the ASHRAE standard were used and for the design of the underground heat exchanger, references of designs recommended through experimental tests in other research works are included, together with internal fluid methodology and one-dimensional heat transfer. It includes elements that can help improve the dissipation of energy into the subsurface and maintain transfer properties as stable as possible. This design is designed for the air conditioning of a classroom of normal dimensions that are used in the University and therefore avoid the energy consumption of conventional air conditioning equipment.
Keywords: geothermal energy, renewable source, underground energy storage, air conditioning